Mathematical statistics and probability: 23.3. bis 29.3.1980 - Müller, Dietrich Werner; Rost, Hermann (Tagungsbericht, 1980)
R. Ahlswede, Bielefeld; E. Arjas, Oulu; L. Arnold, Bremen; P. F. Blaesild, Aarhus; E. Bolthausen, Berlin; P. L. Davies, Essen; E. Dettweiler, Tübingen; H. Dinges, Frankfurt; B. Ferebee, Heidelberg; J. Franke, Frankfurt; P. Gaenssler, München; H. D. Georgii, Bielefeld; F. Götze, Köln; Ch. Hipp, Köln; J. Hüsler, Bern; Th. Kaijser, Linköping; D. Kappos, Athen; G. Kersting, Berlin; L. le Cam, Berkeley; P. Majer, Budapest; P. Mandl, Prag; P. R. Masani, Pittsburgh; D. W. Müller, Frankfurt; M. Mürmann, Heidelberg; E. Presutti, Roma; W. E. Pruitt, Minneapolis; F. Pukelsheim, Freiburg; H. Rieder, Freiburg; U. Roesler, Göttingen; H. Rost, Heidelberg; G. Sawitzki, Bochum; E. Siebert, Tübingen; H. Strasser, Bayreuth; W. Stute, München; M. Taqqu, Ithaca; E. N. Torgersen, Oslo; I. Wegener, Bielefeld; H. v. Weizsäcker, Kaiserslautern; H. Witting, Freiburg; W. R. van Zwet, Leiden